2019
DOI: 10.3390/jsan8020036
|View full text |Cite
|
Sign up to set email alerts
|

Data-Interpretation Methodologies for Practical Asset-Management

Abstract: Monitoring and interpreting structural response using structural-identification methodologies improves understanding of civil-infrastructure behavior. New sensing devices and inexpensive computation has made model-based data interpretation feasible in engineering practice. Many data-interpretation methodologies, such as Bayesian model updating and residual minimization, involve strong assumptions regarding uncertainty conditions. While much research has been conducted on the scientific development of these met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 83 publications
0
21
0
Order By: Relevance
“…This shows that the bridge possesses significant reserve capacity compared with design calculations. This adds to the growing body of evidence that most structures are safe and possess significant reserve capacity above safety factors (Pasquier et al 2014;Pasquier 2015;Pai et al 2018;Pai et al 2019;Brühwiler 2012) that may be utilized to enhance management actions when quantified (Smith 2016). Appropriate selection of model-classes for structural identification, as outlined in this paper, supports interpretation of monitoring data to improve knowledge of structural behavior and enhance decision making.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…This shows that the bridge possesses significant reserve capacity compared with design calculations. This adds to the growing body of evidence that most structures are safe and possess significant reserve capacity above safety factors (Pasquier et al 2014;Pasquier 2015;Pai et al 2018;Pai et al 2019;Brühwiler 2012) that may be utilized to enhance management actions when quantified (Smith 2016). Appropriate selection of model-classes for structural identification, as outlined in this paper, supports interpretation of monitoring data to improve knowledge of structural behavior and enhance decision making.…”
Section: Discussionmentioning
confidence: 81%
“…In order to compare structural identification results obtained with different model classes and data-interpretation methodologies a validation strategy is required. Pai et al (2019) suggested the use of leave-one-out cross-validation strategy to assess accuracy and precision of structural identification. For the purpose of this paper, accuracy indicates whether or not solutions obtained using structural identification are correct.…”
Section: Background -Error-domain Model Falsificationmentioning
confidence: 99%
“…Methodologies that have been studied comprehensively are residual minimization (RM) (Beven and Binley 1992;Alvin 1997), traditional Bayesian model updating (BMU) (Beck and Katafygiotis 1998;Behmanesh et al, 2015a) and error-domain model falsification (EDMF) Pasquier and Smith 2015). EDMF is a special implementation of BMU that has been developed to be compatible with the form of typically available engineering knowledge and infrastructure evaluation concepts (Pai et al, 2019). These methodologies differ in the criteria used to update models using data and assumptions related to quantification of uncertainties.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, primary-parameter selection has been carried out using sensitivity analysis based on linear-regression models [9,10]. However, civil-infrastructure responses may not have a linear relationship with model parameters such as boundary conditions [11]. Recently, methods based on shrinkage [12] and clustering [13] have been introduced.…”
Section: Introductionmentioning
confidence: 99%